(−)-Epigallocatechin-3-gallate inhibits Met signaling, proliferation, and invasiveness in human colon cancer cells - Larsen, Christine A. (2010)
The Met receptor tyrosine kinase is deregulated in a variety of cancers and is correlated with advanced stage and poor prognosis. Thus, Met has been identified as an attractive candidate for targeted therapy. We compared the tea polyphenol (−)-epigallocatechin-3-gallate (EGCG) and a specific Met inhibitor, SU11274, as suppressing agents of Met signaling in HCT116 human colon cancer cells. Treatment with hepatocyte growth factor increased phospho-Met levels, and this was inhibited in a concentration-dependent manner by EGCG and SU11274 (IC(50) 3.0 vs 0.05 µM, respectively). Downstream activation of Erk and Akt signaling pathways also was suppressed. Both compounds at a concentration of 5 µM lowered cell viability and proliferation, with EGCG being more effective than SU11274, and the invasion of colon cancer cells in Matrigel assays was strongly inhibited. These findings are discussed in the context of the pleiotropic effects of tea catechins, their tissue metabolite levels, and the potential to inhibit colon cancer metastasis and invasion.